Study on the Recognition and Interpretation of the World Heritage Criterion (ii) “an important interchange 12 Study on the Recognition and Interpretation of the of human values” - An , Semina (Restauro Archeologico, 2023)
Criterion (ii) of the 10 World Heritage Criteria describes heritage as the result of "interchange" between different cultures. The definition of criterion (ii) was modified from "influence" to " interchange" by the 1996 Operational Guide- lines. It is understandable that the view of World Heritage on cultural heritage has also changed from "one direction" cultural impact to "cultural interaction". Half a century after the adoption of the World Heritage Convention, it is necessary to review whether this criterion is properly applied to cultural heritage. But, for a considerable number of listed sites, there is a gap in the recognition and interpretation of the value of criterion (ii) and the site. This paper recognizes the basic notion of "exchange of human values”, which has not been studied before and uses the evolutionary chronology of criterion (ii) to interpret the intent of the change. The interpretation identifies the problem and discusses future considerations for criterion (ii).